ANALYSIS OF OPTIMAL PORTFOLIO FORMATION USING SINGLE INDEX MODEL ON STOCKS INCLUDED IN THE LQ 45 MARKET INDEX ON THE INDONESIA STOCK EXCHANGE - Eka Febrianti; Muchriana Muchran; Asri Jaya (AJAR, 2022)
This study aims to determine the optimal stock portfolio using a single index model that is included in the LQ 45 index in the 2017 - 2021 period using the Single Index Model method. This study also aims to calculate the amount of return that will be generated when forming an optimal stock portfolio. The sample used in this study consisted of 28 fixed stocks that were included in the LQ 45 index between 2017 and 2021. The type of research used was descriptive quantitative. The data used in this research is quantitative data. The data used in this research is secondary data. Data analysis was performed using a single index model and calculations were performed using Microsoft Excel program. The data collection method used in this study uses documentation techniques. The results of this study indicate that: There are eight stocks included in the optimal stock portfolio based on the Single Index Model method, namely ADRO, BBRI, EXCL, ICBP, PGAS, PTPP, UNVR, WIKA. The ratio of funds worth investing in these stocks is ADRO 8%, BBRI 32%, EXCL 10%, ICBP 13%, PGAS 30%, PTPP 67%, UNVR 59%, WIKA 7%.